An application of non-ordinary state-based peridynamics theory in cutting process modelling of unidirectional carbon fiber reinforced polymer material. (15th October 2019) - Shang, Shuai; Qin, Xuda; Li, Hao; Cao, Xingfeng
Abstract: The usage of carbon-fiber-reinforced polymer (CFRP) composite keeps increasing in modern industries. However, because of the complexity of CFRP structure, the analysis for CFRP failure process, especially for machining process, is quite difficult. This paper presents a non-ordinary state-based peridynamic approach that can be applied to CFRP machining analysis. In order to describe the composite's anisotropy, fiber bond and matrix bond is first introduced in this approach. For describing the failure characteristic of composite, the Maximum stress failure criteria and Hashin failure criteria is then incorporated into the state-based peridynamic approach. Finally, the contact state between tool and workpiece is detected by utilizing the penalty method in modeling the machining process. To demonstrate the effectiveness of the present method, tension and cutting experiments are conducted as well.